The Cauchy problem for a generalized Camassa–Holm equation with the velocity potential. Issue 3 (17th February 2018) - Lin, Bohuan; Yin, Zhaoyang
Abstract: In this paper, we discuss a generalized Camassa–Holm equation whose solutions are velocity potentials of the classical Camassa–Holm equation. By exploiting the connection between these two equations, we first establish the local well-posedness of the new equation in the Besov spaces and deduce several blow-up criteria and blow-up results. Then, we investigate the existence of global strong solutions and present a class of cuspon weak solutions for the new equation.